Chronic Diarrhoea: A Rare Presentation Of Vitamin B12 Deficiency Anemia In Children - Shrestha, Pun Narayan; Khanal, Bipin; Joshi, Prakash (Journal of Nepal Paediatric Society, 2021)
Vitamin B12 deficiency in children often under reported and usually presents with nonspecific manifestations like neuropsychiatric symptoms, anaemia, glossitis and chronic diarrhoea. Vegetarianism, minimal intake of animal products, poverty and malnutrition may lead to vitamin B12 deficiency. Laboratory reports often show pancytopenia, megaloblasts in bone marrow and low serum cynocobalamine. Injectable vitamin B12 is the treatment of choice. We would like to highlight this case report in view of vitamin B12 deficiency presenting as diarrhoea.